Modification of the materials of the welded zone in the ultra‑deep penetration mode - Yu. S. Usherenko; S. M. Usherenko; A. L. Tarasevich; A. N. Panko (Литьë и металлургия, 2022)
The possibility of chemical elements fusion within the framework of the ultra‑deep penetration technique is shown. When microparticle clots move in a closed welding zone system, additional energy is generated during thermonuclear fusion. Fibers (channels) doped with synthesized materials are formed. The energy of the electric field in this case is many times higher than the energy of the clot used to disperse it.